THE USE OF MATHWAY APPLICATION ON DERIVATIVE MATERIAL ON MATHEMATICS LEARNING MOTIVATION IN HIGH SCHOOL - Yuli Amalia; Mik Salmina; Siti Zahara (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Mathematics learning is one of the learning that is difficult for high school students to understand, both in understanding the material and when solving problems such as in derivative material so that students need high learning motivation and are able to help students become more confident in learning mathematics. The purpose of this study was to determine the use of the mathway application on derivative material in mathematics learning for high school students. The method in this study is quantitative quasi-experimental. The data collection techniques used were pretest and posttest tests, as well as questionnaires. The population in this study were all students of grade XI. However, the samples were: students of grade XI IPA 3 (36 people) as the experimental class and students of grade XI IPA 2 (32 people) as the control class. The results of this study showed the provision of pretest and posttest in the experimental class (XI IPA 3) through treatment with the use of the mathway application so that the difference in pretest and posttest values ​​was obtained to see their learning motivation. The learning motivation of the experimental class was 52.61 and for the control class (XI IPA 2) it was 46.31. Furthermore, for the analysis of the questionnaire given to students in the experimental class, the average value of the questionnaire was 74.25 with a good category. The conclusion of this study is that the use of the Mathway application has an effect on the learning motivation of high school students in the derivative material as evidenced by the difference in the pretest-posttest scores of the experimental class and the control class and the average value of the questionnaire. The suggestion in this study is that there needs to be an adjustment to the use of the Mathway application in mathematics learning and it is necessary to conduct a re-examination of the use of the Mathway application to see students' learning motivation in mathematics learning using different materials and methods.